Juridical Analysis and Implementation of Perma 1/2020 in Corruption Crimes : Perma No. 1 of 2020 as an Instrument for Strengthening Judicial Accountability and Restoring Public Sense of Justice - Syarifudin, Urif; Rahmaddani, Imam; Azis, Hasnah (PT FORMOSA CENDEKIA GLOBAL, 2025)
The 1945 Constitution mandates the state to ensure justice and public welfare, encompassing moral values, social ethics, and humanitarian considerations. Public perception of justice, especially in corruption cases, is crucial, as lenient verdicts can erode public trust. President Prabowo emphasized that light sentences for corruptors harm the public’s sense of justice. The rising number of corruption cases has led to a 34-point decline in Indonesia’s Corruption Perceptions Index (CPI) from 2022 to 2023, classifying Indonesia as a “corruption-prone” country. This study analyzes sentencing provisions in Perma No. 1/2020 from a justice perspective, evaluates its implementation, and provides recommendations for fair sentencing. A mixed-method approach (qualitative-quantitative) is used, including correlation tests with SPSS. The results show a significant correlation between state losses and sentence severity in Perma 1/2020. However, its implementation remains weak, with inconsistent judicial rulings leading to sentencing disparities. This study recommends strengthening the implementation of Perma No. 1/2020 to ensure consistency, transparency, and fairness in corruption sentencing and to restore public trust in justice.